Particle Leaching Rates from a Loamy Soil Are Controlled by the Mineral Fines Content and the Degree of Preferential Flow. Issue 6 (1st November 2018) - Norgaard, Trine; Paradelo, Marcos; Moldrup, Per; Katuwal, Sheela; de Jonge, Lis W.
Abstract : The mobilization and transport of colloid particles in soils can have negative agronomic and environmental effects. This work investigates the controls of particle release and transport from undisturbed soil columns sampled from an agricultural, loamy field with clay and silt contents of 0.05 to 0.14 and 0.07 to 0.16 kg kg −1, respectively. Forty‐five soil columns (20 × 20 cm) were collected from the field and exposed to a constant irrigation of 10 mm h −1 for 8 h. The accumulated mass of particles in the outflow from each column was highly correlated ( r = 0.88) with the volumetric mass of fines (MFvol ). The MFvol is defined as the sum of clay and fine silt (<20 μm) multiplied by the soil bulk density and divided by the particle density of the mineral fines. Thereby, MFvol represents both the particle source available for mobilization and leaching and an indicator of soil structure. The particle release process showed two linear particle release rates. Although the two particle release rates were distinctly different, both were strongly correlated with MFvol . The difference between the two rates was related to the degree of preferential flow characterized by the 5% arrival time of an applied tracer pulse. Soil columns with a longer 5% arrival time (less preferential flow) showed a distinct difference between the two rates, whereas soil columns with a short 5% arrival time and fast water transport showed resemblance between the two particle release rates. Thus, the combined effects of particle source, type, and pathways (via soil structure and compaction) need consideration to understand and predict particle transport dynamics through intact topsoil. Core Ideas: Particle leaching from intact soil columns depends on both texture and structure. Volumetric content of mineral fines well predicts particle mobilization and transport. During preferential flow conditions, the particle leaching rate is relatively constant. Varying particle mobilization rates occur mainly during matrix‐dominated flow.